Infrastructure Investments Regulatory Treatment and Optimal Capital Allocation Under Solvency II - Regele, Fabian (BestMasters,, 2018)
Fabian Regele examines the appropriateness of the current regulatory treatment and the general suitability of unlisted infrastructure equity investments for the investment purposes of insurance companies. The employed valuation model of a stylized infrastructure asset delivers sound economic results and is consistent with the typical J-curve effect of the cumulative cash flows of these assets. In the context of a portfolio optimization, the infrastructure asset improves the insurance company's solvency situation by lowering its default probability and increasing its solvency ratio. In regard to the asset's risk contribution, there is a time-variant occurrence of certain risk channels during its lifecycle that leads to substantial differences in the risk exposure of the insurance company. Contents • Overview of the Infrastructure Asset Class • Valuation Model of a Direct Infrastructure Asset • Optimal Capital Allocation and Solvency Capital Requirements for the Insurance Company • Adjustment of the Infrastructure Asset's Regulatory Capital Charge Target Groups • Students and academics with a focus on insurance regulation, business administration, asset management • Insurance regulators and supervisors, portfolio/risk managers The Author Fabian Regele is a research assistant and doctoral student at the International Center for Insurance Regulation of the Goethe University Frankfurt. His research primarily focuses on insurance regulation and systemic risk of financial institutions.